Environment and the Lifetime of Tropical Deep Convection in a Cloud-Permitting Regional Model Simulation - Hagos, Samson; Feng, Zhe; McFarlane, Sally; Leung, L. Ruby (Journal of the atmospheric sciences, 2013)
By applying a cloud-tracking algorithm to tropical convective systems in a regional high-resolution model simulation, this study documents the environmental conditions before and after convective systems are initiated over ocean and land by following them during their lifetime. The comparative roles of various mechanisms of convection–environment interaction on the longevity of convective systems are quantified. The statistics of lifetime, maximum area, and propagation speed of the simulated deep convection agree well with geostationary satellite observations. Among the environmental variables considered, lifetime of convective systems is found to be most related to midtropospheric moisture before as well as after the initiation of convection. Over ocean, convective systems enhance surface fluxes through the associated cooling and drying of the boundary layer as well as increased wind gusts. This process appears to play a minor positive role in the longevity of systems. For systems of equal lifetime, those over land tend to be more intense than those over ocean especially during the early stages of their life cycle. Both over ocean and land, convection is found to transport momentum vertically to increase low-level shear and decrease upper-level shear, but no discernible effect of shear on the lifetime of the convective systems is found.